Contributions of university extension on the formation of nursing academics - Taisa de Paula Paiva Freitas; Cristiane Cardoso de Paula; Bruna Pase Zanon; Fernando Setembrino Cruz Meirelles; Teresinha Heck Welleir; Stela Maris de Mello Padoin (Universidade Federal de Santa Maria, 2016)
Aim: to analyze the contributions of extension actions in the teaching of egressed students from the extension projects of AIDS, education and citizenship Program. Method: quantitative cross-sectional study. The participating population of the study was 43 egressed students from the extension project, linked to the nursing course of a Federal University. Data colletion occured through questionnaires that were sent by email from April to May, 2015 and were analyzed by Prictive Analytics software program. Results: the autonomies obtained after the participation in extension activities wesr emphasized, such as the autonomy on personal development, related to their own learning process, the teamwork, the mutual respect in the work enviroment and the academic improvement, since they had the opportunity to perform activities that are not found in the curriculum. Conclusion: The participation of academics in extension projects increases the responsibility to contribute decisively to social, individual and collective changes